2021
DOI: 10.3389/fmars.2020.613647
|View full text |Cite
|
Sign up to set email alerts
|

Macro and Microstructural Characteristics of North Atlantic Deep-Sea Sponges as Bioinspired Models for Tissue Engineering Scaffolding

Abstract: Sponges occur ubiquitously in the marine realm and in some deep-sea areas they dominate the benthic communities forming complex biogenic habitats – sponge grounds, aggregations, gardens and reefs. However, deep-sea sponges and sponge-grounds are still poorly investigated with regards to biotechnological potential in support of a Blue growth strategy. Under the scope of this study, five dominant North Atlantic deep-sea sponges, were characterized to elucidate promising applications in human health, namely for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 114 publications
(125 reference statements)
0
6
0
Order By: Relevance
“…A recent study indicated that the skeletal motifs of the deep-sea glass sponge Euplectella aspergillum could reduce the overall hydrodynamic stress and support coherent internal recirculation patterns at low flow velocity, revealing the mechanisms of its extraordinary adaptation to live in the abyss. 167 In recent years, researchers have shown significant interest in studying the structure and hierarchical assembly of the siliceous skeleton of glass sponges, [168][169][170][171] leading to exciting advances and deeper insights into glass sponges.…”
Section: àmentioning
confidence: 99%
“…A recent study indicated that the skeletal motifs of the deep-sea glass sponge Euplectella aspergillum could reduce the overall hydrodynamic stress and support coherent internal recirculation patterns at low flow velocity, revealing the mechanisms of its extraordinary adaptation to live in the abyss. 167 In recent years, researchers have shown significant interest in studying the structure and hierarchical assembly of the siliceous skeleton of glass sponges, [168][169][170][171] leading to exciting advances and deeper insights into glass sponges.…”
Section: àmentioning
confidence: 99%
“…The former is frequently not available, and the latter two carry risk of disease transmission and host rejection, posing a major biomedical challenge ( 271 ). Siliceous scaffolds provide an attractive source of either xenografts or biomimetic constructs inspired by their structure ( 268 ). A recent study found diversity in porosity and pore size among representative deep-sea sponge species ( Geodia barretti, Geodia atlantica, Stelletta normani, Phakellia ventilabrum , and Axinella infundibuliformis ), suggesting varying inspirations for tissue engineering applications ( 268 ).…”
Section: The Deep Sea As a Source Of Inspirationmentioning
confidence: 99%
“…Deep-sea sponges have attracted intense interest, as they are known to form siliceous skeletons characterized by high levels of porosity that can act as natural tissue scaffolds [247][248][249][250] . A challenge of treating bone defects in humans is the need for bone substitution materials, with the traditional sources being the patient themself (autogenous grafts), other individuals of the same species (allograft materials), or non-human species (xenografts) 251 .…”
Section: Skeletons Of the Deep -Deep-sea Spongesmentioning
confidence: 99%
“…A powerful and highly accurate tool for digitizing real geometries, among other studies, is computational microtomography (micro-CT) scanners, where 3D reconstruction volumes can be obtained layer by layer, and then mesh this geometry in order to perform a numerical simulation using the FEM to evaluate the mechanical response with high accuracy ( Arabnejad et al, 2016 ; Wu et al, 2018 ; Cheong et al, 2020 ). Recent studies have used this technology to examine the internal architecture of marine organisms, evaluating porosity, pore size and interconnectivity, and anisotropic features ( Martins et al, 2021 ). The model generated using micro-CT technology allows to perform an inverse adjustment of the mechanical properties in these complex geometries and thus compare the experimental mechanical response of the tests with the corresponding numerical simulation ( Bustos et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%